1984
DOI: 10.2307/3899153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Livestock Grazing on Infiltration Rates, Edwards Plateau of Texas

Abstract: The influence of short duration grazing (SDG), moderate continuous grazing (MCG), heavy continuous graxlnr (HCG). and communities was evahtated over a 2Ormonth pe& on the Texas Agricultural Research Station, located near Sonora in the Edwards Plateau, Texas. A combination of cattle, sheep, and goats were used in each grazing treatment. Infiltration rates were consistently less in the midgrass (bunchgrass) than in the shortgrass (sodgrass) community. The HCG pasture was severely overgraxed and htfiltration rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…This is partly attributed to the presence of the predominantly allophanic soil in the former area and the ability of allophanic soil to bind organic colloids and phosphate anions (Fieldes 1968a). Various studies have demonstrated that soil texture, soil organic matter content, and soil P retention capacity can inversely govern the extent of water drainage, soil compaction, and P runoff (McCalla et al 1984;Cooke 1988;Naeh et al 1990aNaeh et al , 1990b. Thus, the effects of treading damage on soil compaction and surface runoff of SS, N, and P are likely to be more pronounced in the steep inter-track plots than in the easy-contoured plots.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is partly attributed to the presence of the predominantly allophanic soil in the former area and the ability of allophanic soil to bind organic colloids and phosphate anions (Fieldes 1968a). Various studies have demonstrated that soil texture, soil organic matter content, and soil P retention capacity can inversely govern the extent of water drainage, soil compaction, and P runoff (McCalla et al 1984;Cooke 1988;Naeh et al 1990aNaeh et al , 1990b. Thus, the effects of treading damage on soil compaction and surface runoff of SS, N, and P are likely to be more pronounced in the steep inter-track plots than in the easy-contoured plots.…”
Section: Resultsmentioning
confidence: 99%
“…The coarser-textured soil, the lower slope, the higher aggregate stability, and the higher soil organic matter content in the latter (Table 1) could account for the observed higher water infiltration rate (Fieldes 1968a;Van Haveren 1983;McCalla et al 1984). Water infiltration rate was higher in undamaged plots than in damaged plots (Table 1), particularly in the steep inter-track zone.…”
Section: Intermediate Effects On Water Infiltration Rate Sediment Prmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies at different locations have been quite consistent in showing that hoof action from having a large number of animals on a small area for short time periods reduced rather than increased infiltration (McCalla et al 1984, Thurow et al 1986, Weltz and Wood 1986, Warren et al 1986, Pluhar et al 1987. These same studies have also been consistent in showing short-duration grazing increased erosion compared to continuous or seasonlong grazing.…”
Section: Hoof Action and Soilsmentioning
confidence: 68%